Levitation of delocalized states at weak magnetic field: critical exponents and phase diagram - Kagalovsky, V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
We study numerically the form of the critical line in the disorder–magnetic field phase diagram of the p–qnetwork model, constructed to study the levitation of extended states at weak magnetic fields. We use oneparameterscaling, keeping either q (related to magnetic field) or p (related to energy) constant, to calculate two critical exponents, describing the divergence of the localization length in each case. The ratio of those two exponents defines the form of the critical line close to zero magnetic field.